FILOSOFI PENDIDIKAN KI HADJAR DEWANTARA DALAM MENJAWAB TANTANGAN PENDIDIKAN KONTEMPORER - Andaru Krisna Jati; Eko Handoyo; Tutik Wijayanti (STKIP Subang, 2026)
Contemporary education faces various complex challenges, ranging from the dominance of technocratic approaches, an excessive orientation towards cognitive achievement, to the risk of dehumanization due to the digitization of education. These conditions demand deep philosophical reflection so that education remains grounded in its fundamental purpose as a process of humanization. This article aims to examine and reconstruct Ki Hadjar Dewantara's ideas on education conceptually and philosophically in response to the challenges of education today. This study uses a qualitative approach with library research. The data sources consist of Ki Hadjar Dewantara's original works as primary sources and various relevant national and international literature as secondary sources. Data analysis was conducted descriptively and analytically with a philosophical-critical approach through data reduction, theme organization, and reflective interpretation. The results of the study show that Ki Hadjar Dewantara's educational thinking emphasizes education as a process of guiding human nature as a whole through a balance of creativity, feeling, and will. The principles of among and the trilogy of educational leadership have strong conceptual relevance to the humanistic pedagogical paradigm, learner-centered learning, and transformative educational leadership. This study confirms that Ki Hadjar Dewantara's thinking is not only historically valuable but also offers an important reflective philosophical framework for reconstructing the direction of national education to remain humanistic, character-building, and contextual amid the dynamics of changing times.